Dampak Digitalisasi Terhadap Umkm Di Kota Jambi: Studi Deskriptif Kualitatif Tentang Persepsi Para Pakar Dan Pelaku Usaha Umkm - Suroto, Suroto (Brida Provinsi Jambi, 2023)
Digitalization has brought about significant changes in the business operational landscape at various levels, including SMEs. This research aims to explore the impact of digitalization on SMEs in Jambi City based on the perspectives of experts and SME business actors. Qualitative research methods were adopted in this study to provide in-depth insight into the impact of digitalization on SMEs. To collect accurate and quality data, this research relies on a Focus Discussion Group (FGD) with 6 experts and individual interviews with 22 SME business owners operating in various business sectors. This research approach follows the COREQ (Consolidated criteria for REporting Qualitative research) Checklist guidelines, which ensures the accuracy and superiority of research results. Data analysis was carried out using ATLAS.ti software which makes it possible to find, code, and manage data from FGDs and individual interviews more efficiently. The results of the analysis identified five main themes of the impact of digitalization on SMEs, namely: Improved Business Management, Marketing and Branding, Technology Challenges, Partnerships and Collaboration, and Customer Experience. It is hoped that this research will provide a better understanding of how digitalization has affected SMEs from various aspects, as well as illustrate the challenges that need to be overcome. The results of this research can be used as a basis or guideline for developing better strategies to support the growth and sustainability of MSMEs in the ever-developing digital era.